Epidemiological Trends and Hotspots of Other Infectious Diarrhea (OID) in Mainland China: A Population-Based Surveillance Study From 2004 to 2017 - Chen, Can; Guan, Zhou; Huang, Chenyang; Jiang, Daixi; Liu, Xiaoxiao; Zhou, Yuqing; Yan, Danying; Zhang, Xiaobao; Zhou, Yiyi; Ding, Cheng; Lan, Lei; Lin, Yushi; et al. (Frontiers in Public Health, 2021)
Background: The incidence of other infectious diarrhea (OID, infectious diarrhea other than cholera, dysentery, and typhoid/paratyphoid) ranked second in class C notifiable disease in China. It has posed a great threat to public health of all age groups. The aim of this study was to investigate the epidemiological trends and hotspots of OID in mainland China. Materials and Methods: Incidence and mortality data for OID stratified by date, age and region from 2004 to 2017 was extracted from the data-center of China public health science. Joinpoint regression and space-time analyses were performed to explore the epidemiological trends and hotspots of OID. Results: The average annual incidence of OID was 60.64 /100,000 and it showed an increased trend in the mainland China especially after 2006 (APC = 4.12, 95CI%: 2.06-6.21). Children of 0-4 year age group accounts for 60.00% (5,820,897/11,414,247) of all cases and its incidence continuously increased though 2004-2017 (APC = 6.65, 95CI%: 4.39-8.96). The first-level spatial and temporal aggregation areas were located in Beijing and Tianjin, with the gathering time from 2005/1/1 to 2011/12/31 (RR = 5.52, LLR = 572893.59, P<0.001). The secondary spatial and temporal aggregation areas covered Guangdong, Guangxi, Hainan and Guizhou from 2011/1/1 to 2017/12/31 (RR= 1.98, LLR = 242292.72, P<0.001). OID of Tianjin and Beijing presented a decreased trend since 2006. However, the incidence of OID in Guangdong, Guangxi, Hainan and Guizhou showed increased trends through 2004-2017. Conclusion: Our study showed that OID showed a constantly increasing trend and brought considerable burden in China especially in the 0-4 age group. The high-risk periods and clusters of regions for OID were identified, which will help government develop disease-specific and location-specific interventive measures.